(untitled) (Simbiótica. Revista Eletrônica, 2024)
The present article problematizes the possibilities of dialogues and intersections between the fields of historical-sociological narrative, literature, and psychoanalysis. The point of intersection is the listening to the possibilities of social bonds in the Polis. We propose to discuss the relationships between violence against femininity, power, and subjectivity. We conclude that the body is far from being a given of nature, nor an individualized entity, but is shaped by culture and the social making-being. The body encompasses different conceptions, forms of management, and modes of performance and staging. We point to the female body not as a cause, but rather as a result of unequal power relations.